Czy specyficzne słownictwo dawnych polskich utworów fantastycznonaukowych może być przedmiotem zainteresowania leksykografa? - Kajtoch, Wojciech (Colloquia Litteraria, 2023)
The article poses the problem of the sense of including words characteristic of science fiction in Polish language dictionaries. It characterizes the vocabulary (based on Juliusz Braun’s novel „When the Moon Dies”), and finally considers the possibility of creating a separate dictionary collecting lexis of this kind